Preparation and in situ use of unstable N-alkyl α-diazo-γ-butyrolactams in RhII-catalyzed X–H insertion reactions - Eremeyeva, Maria; Zhukovsky, Daniil; Dar’in, Dmitry; Krasavin, Mikhail (Beilstein Journal of Organic Chemistry, 2020)
N-Alkyl α-diazo-γ-butyrolactams, previously found to be unstable and to undergo unproductive dimerization to bishydrazones, were successfully converted immediately to various X–H insertion products with alcohols, aromatic amines and thiols via an in situ RhII-catalyzed reaction. With aliphatic amines or unreactive, sterically hindered anilines, the reactions tended to yield enamine adducts.
Keywords: in situ reactions; N-alkyl 2-pyrrolidones; RhII-catalyzed insertion reactions; stability of diazo compounds

(untitled) - Zhukovsky, D.; Dar'in, D.; Kantin, G.; Krasavin, M. (Eur. J. Org. Chem., 2019)

(untitled) - Zhukovsky, D.; Dar'in, D.; Krasavin, M. (Eur. J. Org. Chem., 2019)

(untitled) - Barkhatova, D.; Zhukovsky, D.; Dar'in, D.; Krasavin, M. (Eur. J. Org. Chem., 2019)

(untitled) - Kantin, G.; Dar'in, D.; Krasavin, M. (Eur. J. Org. Chem., 2018)

(untitled) - Clarke, L. A.; Ring, A.; Ford, A.; Sinha, A. S.; Lawrence, S. E.; Maguire, A. R. (Org. Biomol. Chem., 2014)

(untitled) - Hansen, S. R.; Spangler, J. E.; Hansen, J. H.; Davies, H. M. L. (Org. Lett., 2012)